ANALISIS KESULITAN SISWA DALAM MENYELESAIKAN SOAL OPERASI HITUNG BILANGAN CACAH DI KELAS III SD NEGERI 2 PAGAR AIR KABUPATEN ACEH BESAR - Arlida Yanti; Tursinawati; Linda Vitoria (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Learning difficulties in mathematics are a common problem experienced by elementary school students, particularly in whole number operations, including addition, subtraction, multiplication, and division. These difficulties can hinder students’ conceptual understanding and their ability to solve both direct and word problems. This study aims to describe the forms of students’ difficulties and the factors causing these difficulties in solving whole number operation problems among third-grade students at SD Negeri 2 Pagar Air, Aceh Besar Regency. This research employed a qualitative approach with a descriptive research type. The subjects of this study were 16 third-grade students. Data collection techniques included tests, questionnaires, and interviews. The data analysis technique used the Miles and Huberman model, which consists of data reduction, data display, and conclusion drawing. The results showed that the overall difficulty level of students in solving whole number operation problems was categorized as very high. Specifically, the highest difficulties were found in problem-solving skills (91.87%), arithmetic skills (90.46%), and conceptual understanding (82.5%). The factors causing these difficulties consisted of internal and external factors, with the most dominant factors being school learning facilities, peer influence, and teaching approaches. Thus, it can be concluded that students’ difficulties in solving whole number operation problems are still very high and are more dominantly influenced by external factors.